2011
DOI: 10.1073/pnas.1019691108
|View full text |Cite
|
Sign up to set email alerts
|

Silicon carbonate phase formed from carbon dioxide and silica under pressure

Abstract: The discovery of nonmolecular carbon dioxide under high-pressure conditions shows that there are remarkable analogies between this important substance and other group IV oxides. A natural and long-standing question is whether compounds between CO 2 and SiO 2 are possible. Under ambient conditions, CO 2 and SiO 2 are thermodynamically stable and do not react with each other. We show that reactions occur at high pressures indicating that silica can behave in a manner similar to ionic metal oxides that form carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
73
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(84 citation statements)
references
References 33 publications
9
73
0
Order By: Relevance
“…The structural search is carried out for all solids under strong compression, i.e., under a high pressure of 20 GPa. This pressure is close to the reactive pressure of SiO 2 and CO 2 implemented in the experiment [20].…”
Section: Methodssupporting
confidence: 81%
See 1 more Smart Citation
“…The structural search is carried out for all solids under strong compression, i.e., under a high pressure of 20 GPa. This pressure is close to the reactive pressure of SiO 2 and CO 2 implemented in the experiment [20].…”
Section: Methodssupporting
confidence: 81%
“…However, the calculated formation energies for all the structures predicted are positive, indicating that the predicted structures are all metastable thus far. Recently, Santoro et al [20] successfully synthesized a silicon-carbonate phase through the reaction between CO 2 and SiO 2 under highpressure conditions, which demonstrates that it is possible to synthesize various crystalline phases of Si x C 1−x O 2 compounds in the laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…The substitution of tetrahedral (sp 3 ) carbon for silicon in silicate minerals and melts has often been suggested as a possibility at high pressure (5-13), but there was little experimental evidence for it until recent phase equilibrium studies indicated that CO 2 can undergo transformation from a molecular gas to an extended solid at very high pressure and temperature to form a cristobalite-like structure consisting of a network of corner-sharing CO 4 tetrahedra (13,14). Recent studies have also indicated the possibility of a chemical reaction between SiO 2 and CO 2 to form a silicon carbonate phase under pressure (12) and the possibility of amorphous solid phases (7,11). However, the experimental results and their structural interpretations have remained somewhat controversial, and, in any event, such reactions appear to require pressures near a megabar, probably making them unimportant for most of the crust and mantle.…”
mentioning
confidence: 99%
“…Experimental (11) and theoretical (13) works suggest that CO 2 is produced at high pressure (P) and temperature (T) during decarbonating reactions with silica in subducted basalts and is subsequently released into the ocean and atmosphere during volcanic activity (8). Moreover, reactions between silica and free CO 2 may also take place under such conditions, leading to the formation of silicon carbonates (15). Whether free CO 2 is stable or decomposes into oxygen and diamond in the mantle is currently unclear (11,12,16,17).…”
mentioning
confidence: 99%